2006
DOI: 10.1038/sj.ijo.0803319
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and abdominal obesity among Finnish adults from 1992 to 2002

Abstract: Objective: To examine 10-year changes in waist circumference (WC) and identify socio-economic groups having higher WC than expected by their body mass index (BMI). Design: Population based cross-sectional surveys carried out in four regions of Finland in 1992Finland in , 1997Finland in and 2002. Subjects: A total of 9026 women and 8173 men, aged 25-64 years. Measurements: Waist circumference, BMI, socio-economic indicators (education, household income, employment status, marital status) and health behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
3
25
0
2
Order By: Relevance
“…They also show that WC obesity is increasing more rapidly than BMI obesity and, while BMI obesity is more prevalent among men, WC obesity is more prevalent among women. These findings agree with those of several recent studies carried out in Northern Europe 21,27 . There are few studies that examine the possible relationship of SES and overweight and obesity prevalence, and even fewer for the actual distribution of its prevalence into the SES groups 21,26,28 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…They also show that WC obesity is increasing more rapidly than BMI obesity and, while BMI obesity is more prevalent among men, WC obesity is more prevalent among women. These findings agree with those of several recent studies carried out in Northern Europe 21,27 . There are few studies that examine the possible relationship of SES and overweight and obesity prevalence, and even fewer for the actual distribution of its prevalence into the SES groups 21,26,28 .…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, the two measures are highly correlated 21 . It has been shown that changes in WC accompany changes in cardiovascular risk factors especially in the elderly 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unemployment has also been linked to a higher prevalence of risky health behaviors, including problematic alcohol consumption and smoking [40,94]; a higher rate of all-cause mortality [95]; and higher rates of cardiovascular illnesses [96] and metabolic disturbances [97], including general obesity [97][98][99] and abdominal obesity [40,100].…”
Section: Unemploymentmentioning
confidence: 99%